2012
DOI: 10.1245/s10434-012-2295-5
|View full text |Cite
|
Sign up to set email alerts
|

HOXB9 Expression Promoting Tumor Cell Proliferation and Angiogenesis Is Associated with Clinical Outcomes in Breast Cancer Patients

Abstract: HOXB9 expression, which promotes tumor proliferation and angiogenesis, is a significant prognostic factor in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 32 publications
8
41
1
Order By: Relevance
“…HOXB9 mRNA expression was significantly higher in poorly differentiated adenocarcinomas than in highly and moderately differentiated types of adenocarcinomas (Figure 1c) and was highly related to liver metastasis (Additional file 1: Figure S1b). Moreover, although HOXB9 did not affect the disease free survival after surgery, increased HOXB9 expression in colorectal cancer was significantly associated with a poor prognosis in overall survival (Figure 1d), as previously reported for breast cancer [14]. …”
Section: Resultssupporting
confidence: 83%
“…HOXB9 mRNA expression was significantly higher in poorly differentiated adenocarcinomas than in highly and moderately differentiated types of adenocarcinomas (Figure 1c) and was highly related to liver metastasis (Additional file 1: Figure S1b). Moreover, although HOXB9 did not affect the disease free survival after surgery, increased HOXB9 expression in colorectal cancer was significantly associated with a poor prognosis in overall survival (Figure 1d), as previously reported for breast cancer [14]. …”
Section: Resultssupporting
confidence: 83%
“…In our previous study, we examined 141 breast cancer tissues for HOXB9 expression by immunohistochemistry [16]. We used exactly the same cohort of tissue samples to stain for E2F1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Of 155 consecutive, invasive ductal carcinoma patients who were diagnosed as having stage I, II, or III disease and who had not received any treatment before surgery, 139 paraffin-embedded tissue specimens were available for immunohistochemical (IHC) assessment [16]. Written informed consent was taken and the study was approved by the ethics committee of the School of Medicine of Keio University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their critical roles in development, increasing numbers of studies demonstrated that HOX family genes are associated with tumorigenicity (Chen and Sukumar, 2003; Grier et al , 2005; Shah and Sukumar, 2010) and progression including tumour growth and angiogenesis (Chen and Sukumar, 2003; Rhoads et al , 2005; Winnik et al , 2009; Sun et al , 2013). HOXB9 was known to induce tumour angiogenesis, invasion and lung metastasis in breast cancer (Hayashida et al , 2010), as well as being an important prognostic factor for clinical outcomes of breast cancer patients (Chiba et al , 2012; Morgan et al , 2012; Seki et al , 2012; Shrestha et al , 2012). HOXB9 was also found to induce epithelial-to-mesenchymal transition (EMT), a process that is associated with tumour invasion and resistance to chemotherapeutic drugs and radiations by accelerating DNA damage responses (Nguyen et al , 2009; Hayashida et al , 2010).…”
mentioning
confidence: 99%